Food Culture Integration in Menu Plan for a Sustainable Homestay Business - PUSIRAN, Arif Kamisan; JANIN, Yuzainy; MARZUKI, Kamarul Mizal; BOONYANMETHAPORN, Watsida (Journal of Environmental Management and Tourism, 2021)
Other than providing overnight stays and local activities, the provision of food and beverage is an important aspect in the homestay business. The food and beverage aspect of a homestay has the potential of being a crucial contributing factor towards a guest’s experience whilst ensuring optimal monetary return to the homestay operators. This paper presents the findings on meal offerings provided by four homestay operators at Mantanani Island, an island off the Kota Belud coast of Sabah. This study also highlights the importance of food as an element of local culture and as an expression of the history, habits and traditions of a community. Discussions are pinned on rationalising the differences in meal offerings among operators and how this would implicate the operators’ profit margins, as well as how the local culture reflects the menu offered by the homestay participants.  Finally, recommendations for improvement on meal plans are proposed to enhance the economic benefits of these operators without compromising guest experience